Very efficient multi-photon absorption in porphyrins with extended π-conjugation - Drobizhev, M; Karotki, A; Anderson, H; Rebane, A (2003)
We report a dramatic enhancement of multiphoton absorption in porphyrins in near-infrared range. This is achieved by the near-resonance conditions for each photon to be absorbed and by an extension of molecular π-conjugation.